A new Mucocutaneous Activity Index for Behcet's disease - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2014)
Objective. Patient-reported outcomes are increasingly accepted to be major domains in chronic disorders. The aim of this study was to develop a patient-derived disease activity index in Behcet's disease (BD). Methods. One hundred and seventy-seven BD patients (M/F: 69/108) were included in the study. Data were collected by clinical examination and a questionnaire regarding a Mucocutaneous Index (MI) with genital ulcer activity (GI), erythema nodosum activity (El) and the composite index (Cl) for oral ulcers, as subscales of it. Self-reported treatment evaluation was carried out as criterion validity. Patients whose symptoms completely disappeared or decreased significantly, were categorised as improved group, others were classified as non-improved group. Results. Among the study group, 79.7% of the patients (n=141) were active, whereas 20.3% were inactive (n=36). Scores of Cl, GI, El and MI score were 0+/-0 in inactive ones, whereas scores were 5.65+/-2.36 for CI, 0.81+/-2.34 for GI, 0.91+/-2.35 for El and 6.25+/-5.1 for MI in actives (p=0.000 for all). MI score was significantly higher in non-improved group (65.5%) compared to improved group (34.5%) (p<0.0001). Conclusion. The mucocutaneous activity index may help decision-making process for treatment strategies in BD patients.
Keywords: Behcet's disease; activity; index; mucocutaneous; treatment; symptoms; QUALITY-OF-LIFE; RECURRENT APHTHOUS STOMATITIS; ORAL-HEALTH; CONTROLLED-TRIAL; DOUBLE-BLIND; MANIFESTATIONS; STRATEGIES; SEVERITY; OUTCOMES; ONSET